Penguatan Literasi Digital Guru SMA Muhammadiyah 01 Kota Blitar melalui Pelatihan Penyusunan LKPD Digital dan Media Interaktif - Malahayati, Eva Nurul; Sulistiana, Devita; Fauzi, Adin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
As many as 79.55% of teachers still use digital products from the internet without adapting the learning context, indicating that teachers' digital literacy has not developed in the aspects of productivity and innovation. Training in compiling digital LKPD and developing interactive media is a solution to improve teachers' digital literacy and encourage the implementation of innovative and relevant learning to meet the demands of the 21st century. This community service activity aims to strengthen teachers' digital literacy and improve the quality of learning at SMA Muhammadiyah 01 Kota Blitar. The method used is Participatory Rural Appraisal (PRA) which includes the stages of socialization, training, implementation, and evaluation. Socialization is carried out in coordination with the principal and teachers. Training activities consist of delivering materials and practicing compiling digital LKPD using the Wizer.me and Flipbook applications, as well as interactive media using the Assemblr EDU and Prezi applications. Furthermore, the results are implemented in the learning process in the classroom. Evaluation is carried out on teachers' digital products using student response questionnaires and assessment rubrics for digital LKPD and interactive media. The results of student responses to the implementation of digital products are 91.14%, in the positive category. The results of the digital product assessment, which serves as a benchmark for teachers' digital literacy skills, increased by 13.48% compared to the previous year. Community service activities have significantly contributed to strengthening teachers' digital literacy while providing a more engaging and interactive learning experience for students.